An Analysis of The Discursive Gap in the Ideas and Practices of Musyawarah Mufakat in the Indonesian Nation-State Formation, 1900-1980s - Suwignyo, Agus; Yuliantri, Rhoma Dwi Aria (History Department, Semarang State University and Historian Society of Indonesia, 2023)
The aim of this paper is to examine the existing studies on the Indonesian deliberative mechanism of decision making, musyawarah-mufakat (MM), in the frame of nation-state formation. The 17th of August, 1945 construction of the Indonesian nation-state was based on traditional values despite its modelling of the European modern states by way of colonial legacies. This paper argues that, although scholarly attentions to revisit the ideas and practices of MM have developed very vast over the past four decades, the transformation of MM as a state mechanism has been touched in passing. Consequently, there was a discursive gap in the ideas and practices of MM. By analyzing recent studies on MM and by employing a historical method to explore daily newspapers and official documents published between 1900 and 1980s, this paper shows that the collective nature of MM did represent the taming of the political masses that overrode an individual’s sense of citizenship. Given the notion of unity, the making of MM a state ideology promoted the type of citizenship that had to work contingently with the ideological undertones of the ruling regimes. The Gesellschaft nature of the state enforced a unity as an individual’s social duty, whereas the Gemeinschaft nature of MM promoted a unity as a personal initiative, hence an ambivalence. Nevertheless, the dynamics of people’s citizenship in the practice of MM has become qualitatively compelling over time. Keywords: musyawarah mufakat, citizenship, state formation, Indonesia, twentieth century.Tulisan ini bertujuan untuk mengkaji tentang mekanisme pengambilan keputusan di Indonesia, yakni musyawarah-mufakat (MM), dalam rangka pembentukan negara-bangsa. Pada tanggal 17 Agustus 1945 pembangunan negara-bangsa Indonesia didasarkan pada nilai-nilai tradisional meski mengadaptasi model negara-negara Eropa modern karena warisan kolonial. Tulisan ini berpendapat bahwa meskipun perhatian ilmiah untuk meninjau kembali gagasan dan praktik MM telah berkembang pesat selama empat dekade terakhir, transformasi MM sebagai mesin negara telah disentuh secara sepintas. Dengan menganalisis studi terbaru tentang MM dan menggunakan metode historis untuk mengeksplorasi surat kabar harian dan dokumen resmi yang diterbitkan antara tahun 1900 dan 1980-an, tulisan ini menunjukkan bahwa sifat kolektif MM mewakili penjinakan massa politik yang mengesampingkan rasa kewarganegaraan individu. Mengingat gagasan persatuan, menjadikan MM sebagai ideologi negara yang mempromosikan jenis kewarganegaraan yang harus bekerja secara kontinyu dengan nada ideologis rezim yang berkuasa. Sifat Gesellschaft dari persatuan yang dipaksakan oleh negara sebagai tugas sosial individu, sedangkan sifat Gemeinschaft dari MM mempromosikan persatuan sebagai inisiatif pribadi, karenanya menjadi ambivalensi. Namun demikian, dinamika kewarganegaraan dalam praktik MM menjadi menarik secara kualitatif dari waktu ke waktu.Kata kunci: musyawarah mufakat, kewarganegaraan, pembentukan negara, Indonesia, abad ke dua puluh.